1985
DOI: 10.1177/33.7.3891843
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix of the human thymus: immunofluorescence studies on frozen sections and cultured epithelial cells.

Abstract: The immunohistochemical detection of elements of the human thymic extracellular matrix in situ and in vitro is described. In the normal thymus, the intracapsular and intraseptal fibers were strongly labeled by anti-type I collagen antiserum. Basement membranes bordering the capsule, septae, and perivascular spaces were intensely stained by anti-type IV collagen, anti-fibronectin, and anti-laminm sera. In hyperplastic myasthenia gravis thymuses, the major changes consisted of discontinuities of the basement mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
0
2

Year Published

1988
1988
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 3 publications
7
56
0
2
Order By: Relevance
“…Previous and ours results have demonstrated that (1) TEC derived from normal thymus and grown to organized monolayers, constitutively produce extracellular matrix proteins (laminins, fibronectin and collagen type IV); (2) these cells display two sets of integrins polarized at discrete locations ( § 2 g 1 and § 3 g 1 heterodimers, mostly located at the TEC-TEC boundaries, and § 6 g 4, colocalized with its ligand laminin at the base of the monolayer); and (3) thymocyte or lymphocyte adhesion remodels this pattern, so that § 6 g 4 and § 3 g 1, but not § 2 g 1 integrins, cluster also around individual lymphoid cells, recognizing yet unknown cellular ligands expressed by T cells [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous and ours results have demonstrated that (1) TEC derived from normal thymus and grown to organized monolayers, constitutively produce extracellular matrix proteins (laminins, fibronectin and collagen type IV); (2) these cells display two sets of integrins polarized at discrete locations ( § 2 g 1 and § 3 g 1 heterodimers, mostly located at the TEC-TEC boundaries, and § 6 g 4, colocalized with its ligand laminin at the base of the monolayer); and (3) thymocyte or lymphocyte adhesion remodels this pattern, so that § 6 g 4 and § 3 g 1, but not § 2 g 1 integrins, cluster also around individual lymphoid cells, recognizing yet unknown cellular ligands expressed by T cells [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Both were polyclonal immunosera produced in rabbits by the injection of human plasma fibronectin or laminin purified from the murine Erlich sarcoma [29]. These reagents recognize their corresponding molecules in mouse and human thymuses [30,31]. Goat anti-rabbit IgG antibodies conjugated to fluoresceinisothiocyanate (FITC) were purchased from Pharmingen/Becton-Dickinson.…”
Section: Methodsmentioning
confidence: 99%
“…Thymic epithelial cells have also been shown to be the source of thymic hormones which induce the appearance of maturation markers on thymocytes (10). More recently, the epithelial cells have also been shown to be a source of IL-1 (11).…”
Section: Introductionmentioning
confidence: 99%